HUBUNGAN PEMBERIAN INTERVENSI MUSIK KLASIK BAHASA INGGRIS TERHADAP PENURUNAN TINGKAT DEPRESI PADA IBU HAMIL DI DESA BANGUN REJO KECAMATN TANJUNG MORAWA TAHUN 2025 - Zulkarnain Batubara; Rosmega Rosmega; Muhammad Riezky Laksmana; Imran Saputra Surbakti (Journal of Innovative and Creativity, 2026)
Depression is a mental health disorder whose prevalence has continued to increase in recent years, including among pregnant women. Depression during pregnancy can have various negative consequences, including worsening physical conditions, thus reducing body resistance, hindering the achievement of pregnancy developmental tasks, and reducing the mother's quality of life. Furthermore, depression can also cause emotional stress and economic burdens that are not only felt by pregnant women, but also by their families and supporting environments. This phenomenon was found in pregnant women in Bangun Rejo Village, Tanjung Morawa District, in November 2025. As a non-pharmacological effort to address this condition, a Listening intervention was implemented, namely listening therapy in English classical music and murottal recitation. Research Objective: This study aims to evaluate the effectiveness of listening therapy in English classical music in reducing depression levels in pregnant women in Bangun Rejo Village, Tanjung Morawa District, in 2025. Research Method: This study used a quasi-experimental approach with a pretest–posttest design with a control group. A total of 30 pregnant women were selected as the research sample. Research Results: Statistical analysis using the chi square test showed a significant decrease in depression levels after the intervention, with a p-value of 0.041 (p < 0.05). Furthermore, the analysis of differences in effects between treatments also showed significant results with a p-value of 0.036 (p < 0.05). Conclusion: Based on these findings, it can be concluded that listening to English classical music intervention is effective in reducing depression levels in pregnant women in Bangun Rejo Village, Tanjung Morawa District, in 2025.